Ramanujan’s Expansion for the real valued Harmonic Numbers ; Expansión de Ramanujan para Números Armónicos reales - Haarala Orosco, Mika (2019)
The Ramanujan’s Harmonic Number Expansion plays an important role to accelerate the calculus of the Kijko-Sellevoll function 3 (KS-3) (Haarala and Orosco, 2016). It gives much better performance against the ready-made algorithms. In this paper, we generalized the solution so that it holds also for real valued Harmonic Numbers, knowing that a solution for integer-valued numbers was given. It means that we can use Ramanujan’s Harmonic Number. La expansión de números armónicos de Ramanujan, juega un importante papel para acelerar el cálculo de la Función 3 de Kijko-Sellevoll (Haarala y Orosco, 2016). Tiene un mejor comportamiento que los algoritmos propuestos. En este informe, generalizamos la solución para extender el método a números reales, en el conocimiento que fue propuesta una solución para números enteros. Esto implica que podemos usar la expansión por números armónicos de Ramanujan.